PENGARUH KARAKTERISTIK HABITAT MANGROVE TERHADAP KEPADATAN KEPITING ( SCYLLA SERRATA ) DI PANTAI UTARA KABUPATEN DEMAK, JAWA TENGAH - Haposan Sipayung, Roni (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
Rehabilitation of mangrove forests is very important to maintain ecosystem stability and increase the productivity of mangrove forests. The success of mangrove forest rehabilitation can be seen by the density of mangrove vegetation and the increase in mangrove crabs. Mangrove crab is the main commodity for farming communities because in addition to playing an important role in the mangrove ecosystem, it also has high economic value so it needs to be developed to increase people's income. This research was conducted with the aim of knowing the density of mangrove vegetation and crab density in different planting years and the effect of mangrove habitat characteristics on crab density. The research was conducted in three different planting years, namely 2003, 2005, and 2006. Each planting year consisted of a front zone, a middle zone and a back zone. In each zone a measuring plot with a size of 5 m x 5 m was made to collect data on vegetation density, temperature, mud thickness, salinity, acidity, and dissolved oxygen (DO). Then in the 5 m x 5 m plot, a 1 m x 1 m plot was made to collect data on the number of crabs. Data analysis used regression equation and ANOVA difference test. The results showed that the highest vegetation density was in the back zone of the 2006 planting year with a density of 2160 individuals/ha, while the highest density of crabs was in the 2005 planting year with a density of 12111.11 individuals/ha. Regression analysis showed the effect of temperature, mud thickness and salinity variables on crab density with the equation Y = 3.447 - 0.044X1 - 0.009X2 - 0.230X3 with R = 0.809. In the different ANOVA test, only the thickness of the mud had a significant difference at three years of planting (0.00 < 0.05).